Personal Islamic asset management system using object-oriented approach / Nor Fazlina Iryani Abdul Hamid - Nor Fazlina Iryani , Abdul Hamid (2007)
Islamic asset management system has been implemented over the past few years, but there is no system that combines all types of Islamic assets in one single system. The existing system only focused on the management of the specific asset. In our country, there is only one web-based system for zakat management, whereas the other asset management like fidiah, waqaf and heritage only as a stand-alone system. This will lead to waste of time and effort for users where they have to go to various places to manage their assets. Personal Islamic Asset Management System using Object-oriented approach is a portal that integrates the personal management of Islamic assets which intend to solve all of aforementioned problems. It has detailed information about Islamic asset management including various functions for zakat, heritage, fidiah and kifayah. The Personal Islamic Asset Management System using object-oriented approach also provides the counter information and archived engine to search for related documents. This thesis contributes to the management of personal Islamic assets as well as using object-oriented software engineering. The research methods used are literature review and interviews. The literature review was undertaken to have further understanding of the research problem in order to design the system using object oriented software engineering approach. The interviews were undertaken to add other requirements for Personal Islamic Asset Management System using Object-oriented Approach. The Personal Islamic Asset Management System using Object-oriented Approach is developed using Rational Unified Process (RUP) model and is being implemented using PHP language and MySQL database for the web environment. Usability test and software metrics measurement were done to ensure the system’s usability and system’s metrics in terms of reusability and complexity.